PENGARUH PELAYANAN YANG GAGAL TERHADAP RESPON PERILAKU KONSUMEN - Intan Apurotul Pujiah; Indah Fatmawati (Jurnal Manajemen dan Pemasaran Jasa, 2018)
The study aims to analyze the influence of service failure, disappointment, regret, dissatisfaction, and behavior response. The sample in this research is x airline customers. The samples are 137 respondents chosen by using purposive sampling and collected by questionnaires. Analytical technique used is SEM (Structural Equation Modeling). The results of this study indicate that the service failure has an effect on disappointment and regret. Disappointment has an effect on dissatisfaction. Regret has an effect on the dissatisfaction and behavioral response. Disappointment and dissatisfaction has no effect on behavior response.